SUBIRATS, Marina; CASTELLS, Manuel. Mujeres y hombres ¿Un amor imposible? - Leon, María Antonia García de (Revista Estudos Feministas, 2008)
SUBIRATS, Marina; CASTELLS, Manuel. Mujeres y hombres ¿Un amor imposible?